Glyphosate residues in soil can modify plant resistance to herbivores through changes in leaf quality - Ramula Satu; Kalske Aino; Saikkonen Kari; Helander Marjo (WILEY, 2022)
Glyphosate is the most widely used non-selective herbicide in the world. Glyphosate residues in soil can affect plant quality by modifying plant physiology, hormonal pathways and traits, with potential consequences for plants' interactions with herbivores.
We explored these indirect effects in the context of plant-herbivore interactions in a perennial, nitrogen-fixing herb. We quantified leaf herbivory for glyphosate-exposed and control plants grown in phosphorus-fertilized and non-fertilized soils, and assessed the impacts of glyphosate treatment on traits related to plant resistance against herbivores (leaf trichome density, leaf mass per area) and performance (aboveground biomass, root:shoot ratio, nodule number, nodule activity). Moreover, we conducted a laboratory feeding experiment to compare the palatability of leaves from glyphosate-exposed and control plants to a generalist mollusc herbivore.
Herbivore damage and intensity in situ increased during the growing season regardless of glyphosate or phosphorus treatment. Glyphosate treatment reduced leaf trichome density but had no effect on the other plant traits considered. Herbivore damage was negatively associated with leaf trichome density. The feeding experiment revealed no difference in the feeding probability of mollusc herbivores between glyphosate-exposed and control plants. However, there was an interaction between glyphosate treatment and initial leaf area for leaf consumption by herbivores: leaf consumption increased with increasing leaf area in both groups, but at a lower rate for glyphosate-exposed plants than for control plants.
Our results show that glyphosate residues in soil have the potential to indirectly affect aboveground herbivores through changes in leaf quality, which may have mixed consequences for folivore damage.